Tripropeptin C Blocks the Lipid Cycle of Cell Wall Biosynthesis by Complex Formation with Undecaprenyl Pyrophosphate - Hashizume, Hideki (American Society for Microbiology, 2011)
Tripropeptin C (TPPC) is a naturally occurring cyclic lipodepsipeptide antibiotic produced by a Lysobacter sp. TPPC exhibits potent antibacterial activity against methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE), and penicillin-resistant Streptococcus pneumoniae. This antibiotic also inhibits the incorporation of N-acetylglucosamine into the peptidoglycan of S. aureus at a 50% inhibitory concentration (IC(50)) of 0.7 μM, which is proportional to its MIC (0.87 μM; equivalent to 1.0 μg/ml). Treatment of exponential-phase S. aureus cells with TPPC resulted in accumulation of UDP-MurNAc-pentapeptide in the cytoplasm. The antimicrobial activity of TPPC was weakened by the addition of prenyl pyrophosphates but not by prenyl phosphates, UDP-linked sugars, or the pentapeptide of peptidoglycan. The direct interaction between TPPC and undecaprenyl pyrophosphate (C(55)-PP) was observed by mass spectrometry and thin-layer chromatography analysis, indicating that TPPC can potentially inhibit C(55)-PP phosphatase activity, which plays a crucial role in the lipid cycle of peptidoglycan synthesis. As expected, TPPC inhibits this enzymatic reaction at an IC(50) of 0.03 to 0.1 μM in vitro, as does bacitracin. From the analysis of accumulation of lipid carrier-related compounds, TPPC was found to cause the accumulation of C(55)-PP in situ, leading to the accumulation of a glycine-containing lipid intermediate. This suggested that the TPPC/C(55)-PP complex also inhibits the transglycosylation step or flippase activity, adding to the inhibition of C(55)-PP dephosphorylation. This mode of action is different from that of currently available drugs such as vancomycin, daptomycin, and bacitracin.